Spectrum of HLA associations: the case of medically refractory pediatric acute lymphoblastic leukemia - Klitz, William (Springer-Verlag, 2012)
Although studies of HLA and disease now date back some 50 years, a principled understanding of that relationship has been slow to emerge. Here, we examine the associations of three HLA loci with medically refractory pediatric acute lymphoblastic leukemia (pALL) patients in a case–control study involving 2,438 cases and 41,750 controls. An analysis of alleles from the class I loci, HLA-A and HLA-B, and the class II locus DRB1 illuminates a spectrum of extremely significant allelic associations conferring both predisposition and protection. Genotypes constructed from predisposing, protective, and neutral allelic categories point to an additive mode of disease causation. For all three loci, genotypes homozygous for predisposing alleles are at highest disease risk while the favorable effect of homozygous protective genotypes is less striking. Analysis of A–B and B–DRB1 haplotypes reveals locus-specific differences in disease effects, while that all three loci influence pALL; the influence of HLA-B is greater than that of HLA-A, and the predisposing effect of DRB1 exceeds that of HLA-B. We propose that the continuum in disease susceptibility suggests a system in which many alleles take part in disease predisposition based on differences in binding affinity to one or a few peptides of exogenous origin. This work provides evidence that an immune response mediated by alleles from several HLA loci plays a critical role in the pathogenesis of pALL, adding to the numerous studies pointing to a role for an infectious origin in pALL. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00251-012-0605-5) contains supplementary material, which is available to authorized users.